Pengaruh ENSO Dan IOD Terhadap Curah Hujan Di Pesisir Dan Pegunungan: Studi Kasus Tanjung Priok, DKI Jakarta, Dan Puncak, Jawa Barat - Aslama Afghani, Fadhli; Ravaella Lumbantobing, Glory; Christian Halawa, Jordana; Yehezkiel Sidauruk, Vasco; Giarno (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
As a tropical country, Indonesia has different rainfall distribution and characteristics, influenced by climate variability, including the El Nino Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) phenomena. This study aims to analyze the influence of ENSO and IOD on rainfall, temperature, and humidity in coastal and mountainous areas of Jabodetabek, using observational data from Tanjung Priok Maritime Meteorological Station and Citeko Meteorological Station for the period 1994-2023. The analysis was conducted seasonally using linear regression method to see the trend of climate parameters and Pearson correlation to measure the relationship between climate phenomena and meteorological parameters. The results showed that the ONI index as an indicator of ENSO was in the moderately strong to very strong category in coastal and mountainous areas. In the Positive IOD phase, the correlation with rainfall, temperature, and humidity shows a moderately strong to very strong influence, while in the Negative IOD phase, the impact is weaker. The study also revealed that the El Nino phenomenon tends to reduce rainfall and increase temperatures in coastal areas, while La Nina has more effect on increasing rainfall in mountainous areas. Overall, the ENSO and IOD phenomena have significant impacts on climate variability in these two regions, with differences in influence depending on the phase of each phenomenon.